Existence and sensitivity analysis for nonconvex cubic optimization problems. (3rd July 2022) - Tam, Nguyen Nang; Nghi, Tran Van
Abstract : In this paper, we propose necessary/sufficient conditions for existence of minimizers of nonconvex cubic programming problems via an Eaves type theorem. Directional differentiability of the optimal value function under total perturbation are characterized. Among our proposed assumptions, there are some weaker than the existing assumptions (applied to cubic programming).